Development of reading skills: adopting mobile technology to support learning - Mat Daud, Nuraihan (2010)
Reading is one of the important academic skills and is often associated with students’ academic performance and achievement (Brown, 2007; Bishop, 2003; Krashen, 1995). This suggests that students’ ability to perform successfully in the content area is correlated with their ability to read and comprehend texts. However, the time spent for reading is often limited to a dedicated learning environment and formal curriculum. To ensure that reading can be done regardless of where students are, mobile learning or MLearning through its mobile technologies such as mobile phones may offer another alternative to reading. As many students studying in a university own a mobile phone it can be used for teaching purposes. This research is on the use of mobile learning (Mlearning) particularly short message service (SMS) facility in developing second-language students’ reading skill. It aims to see whether mobile learning can complement traditional reading lesson. The study was conducted on language learners following proficiency courses at CELPAD. SMSes were sent everyday within one semester to the selected students. The study shows that students found the approach interesting and helpful. Some mentioned that receiving the SMS daily has encouraged them to use English or read English materials more often. Others claimed that the activity has enabled them to get access to English wherever they were. They liked receiving extra exposure to English through SMS in addition to classroom learning. Most of them appreciated the fact that they were chosen for the study and expressed hope that this approach will be adopted by the centre. The study also highlighted possible problems when using this technology. Among them are telecommunication networks incompatibility and limitation on the number of characters per message.